2020
DOI: 10.1080/2162402x.2020.1740477
|View full text |Cite
|
Sign up to set email alerts
|

Cancer immunotherapy based on blocking immune suppression mediated by an immune modulator LAIR-1

Abstract: The leukocyte-associated immunoglobulin-like receptor 1 (LAIR-1) is an inhibitory receptor expressed on the majority of peripheral blood mononuclear cells and is important for the regulation of immune responses. The binding of LAIR-1 to its ligands results in the loss of immune function in the tumor microenvironment (TME) and a reduction in T cell function and immune responses of antigen-presenting cells. Using bioinformatics analysis, we showed that LAIR-1 is broadly upregulated in multiple types of cancer. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…LAIR-1 strong association with c-MYC and Cdc42, as we observed in our study, and the concomitant high expression of LAIR-1 in these tumours, suggest that these tumours are highly proliferative and are linked with poor prognosis. This is consistent with a previous study by Xu et al, which demonstrated that high LAIR-1 expression is associated with poor survival in brain, colon, kidney and ovarian cancers [ 22 ]. In line with our findings, LAIR-1 knockdown significantly downregulated proliferation and invasion capabilities in HER2+ BC cell lines.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…LAIR-1 strong association with c-MYC and Cdc42, as we observed in our study, and the concomitant high expression of LAIR-1 in these tumours, suggest that these tumours are highly proliferative and are linked with poor prognosis. This is consistent with a previous study by Xu et al, which demonstrated that high LAIR-1 expression is associated with poor survival in brain, colon, kidney and ovarian cancers [ 22 ]. In line with our findings, LAIR-1 knockdown significantly downregulated proliferation and invasion capabilities in HER2+ BC cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…LAIR-1 is a collagen-binding ITIM-bearing inhibitory receptor and plays an important role in the regulation of the immune system. The tumour microenvironment (TME), including ECM-LAIR-1 interaction, may impair anti-tumour immune responses [ 22 ]. Despite the proven regulatory role of LAIR-1 in immune cells and the high abundance of collagen molecules in the TME in promoting tumour progression, the potential roles of LAIR-1 are less investigated in BC.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was also observed in LAIR1 ( Jingushi et al, 2019 ). Besides, Peng et al (2020) claimed that collagen promotes anti-PD-1/PD-L1 resistance in cancer through LAIR1-dependent CD8 + T cell exhaustion, similar to Xu et al’s findings ( Xu et al, 2020 ). The reports about FMNL1 extensively focused on its role in aggressiveness of many tumors, such as nasopharyngeal carcinoma, leukemia, and ccRCC ( Favaro et al, 2013 ; Chen et al, 2018 ; Zhang et al, 2020 ), while WDFY4 extensively focused on autoimmune diseases ( Kochi et al, 2018 ; Yuan et al, 2018 ; Zhu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 75%
“…However, to further address the question of what the Fc portion of NC410 does, we show that LAIR-2 IgG1 protein with a ‘silenced’ Fc (FES mutation) ( Oganesyan et al, 2008 ) loses anti-tumor activity. A recent independently published study ( Xu et al, 2020 ) also demonstrates anti-tumor activity with an engineered LAIR-2 Fc protein. In this study, the authors engineered an IgG1 with an N297A to prevent binding to Fc receptors, but further mutated it to include T250Q/M428L mutations to increase binding to neonatal FcR (FcRn), which enhances in vivo bioavailability of the protein.…”
Section: Discussionmentioning
confidence: 91%